PREGNANT WOMEN'S READINESS DURING THE COVID-19 PANDEMIC - Tendean, Angelia Friska; Dewi, Arlina; Ering, Cherol Nelson (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
A category of people who are susceptible to COVID-19 infection is pregnant women. The safety of the mother and fetus can be determined in large part by how prepared pregnant women are to give birth. Pregnant women who are mentally and physically prepared for childbirth can have a healthy delivery that includes the removal of the baby, placenta, and membranes. The purpose of this study is to investigate how prepared expectant mothers felt for childbirth during the COVID-19 epidemic. This study employs a qualitative methodology and phenomenology. In this study, 11 informants participated. Face-to-face interviews and semi-structured video were employed in the data collection process. According to the study's findings, there were five key elements in pregnant women's preparedness for childbirth during the COVID-19 pandemic: 1) worry about COVID-19 exposure, 2) keeping healthy throughout the COVID-19 pandemic, 3) adhering to our ancestors' culture, 4) preparing for a safe and comfortable delivery, and 5) receiving the best medical facility services. Pregnant women must maintain their health and carefully arrange their deliveries. Health facilities are crucial in assisting expectant mothers with labor preparation, particularly during the pandemic. During the COVID-19 pandemic, telehealth may be employed as a substitute method of reaching pregnant women.